From Maslow to the environment: investigating the influence of human needs in shaping Eco-Personality - Abu Bakar, Aisyah (Malaysian Institute of Planners, 2023)
This paper discusses Eco-Personality and Lifestyle PL in relation to three notions, namely Human Interdependence HI, Subjective Well-being SWB, and Maslows Hierarchy of Needs HON. Research Questions: Does the fulfilment of human needs have positive impact on PL? Is it possible for PL to develop in spite of unmet human needs? Purpose: This paper examined the level of PL between the difficulty and convenience of fulfilling human needs. Approach: Mann-Whitney U Test was performed to determine the mean variance of PL across the convenience and difficulty of satisfying 24 human needs. Findings: The convenience with which 18 out of 24 human needs could be met increased PL significantly. Moreover, fulfilling these 18 human needs established a conducive environment for nurturing PL. The results also showed that PL did not differ substantially across the convenience and difficulty of satisfying five human needs, which was unlikely to have an impact over PL. Additionally, fulfilling these five human needs and fostering PL were found to develop along different trajectories.